11
1 (7) + (-1)+(-4) =
2 (-21) +63) =
3 (-21 +( 7) +-1) +(-4)=
4 (5)+ (-5)+(I) =
6 (9) + (-5)+(6) +(-2)=
6(3) + (7) + (-9)=
7(8)+(-11)+(-13)=
8(-13)+(17)+(-17)=
9(3)+(4)+(-7)=
10(-11)+(-13)+(-13)+(-17)=
Answers
Answered by
1
Answer:
1) 2
2) 42
3)-19
4) 1
5) 8
6) 1
7) -16
8) -13
9) 0
10) -54
Step-by-step explanation:
hope it helps you
Answered by
1
HERE IS UR ANSWER
HOPE IT HELPS!!
Attachments:
![](https://hi-static.z-dn.net/files/d2d/98a2d3aab2d45dea2172433c57e43c96.jpg)
![](https://hi-static.z-dn.net/files/d3f/79034b70887eef0bd540e82c8e1961b2.jpg)
Similar questions